Fine tuning of the magnetic properties in Mn3-xCoxGa Heusler films near the critical regime - Lee, Kyujoon; Yoo, Woosuk; Nguyen, Quynh Anh T.; Bang, Hyun-Woo; Kim, Hyeonsu; Klaeui, Mathias; Rhim, Sonny H.; Jung, Myung-Hwa (Journal of Alloys and Compounds, 2021)
Tunability of structural and magnetic properties of Mn3-xCoxGa films is presented by Co substitution, where critical behavior emerges 0.37 ≤ x ≤ 0.56 exhibiting a transition from tetragonal hard ferrimagnetic with perpendicular magnetic anisotropy (PMA) to a cubic soft ferrimagnetic phase with in-plane magnetic anisotropy (IMA). In the critical regime, coexisting state of tetragonal and cubic phases possesses significantly low coercive field (HC = 1.9 kOe) with relatively low saturation magnetization (MS = 100 150 emu/cc) while maintaining the PMA. From first-principles calculations, moments of two Mn sites do not change upon Co substitution. However, moments of substituted Co almost vanish in tetragonal while giving around 1 μB in cubic phase, which agrees with overall MS behaviors of the experimental results. These findings not only uncover the hidden magnetic state in Mn3-xCoxGa by altering the parallel and antiparallel coupling between Mn and Co, but also provide an additional degree of freedom for spintronic applications using Mn-based Heusler compounds.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Critical behavior; Heusler compound; Perpendicular magnetic anisotropy